Encapsulation of Japanese grape (Hovenia dulcis) pseudofruits by freeze drying: characterization and antioxidant potential - Rigo, Elisandra; Hanauer, Dalana Cecília; Knakiewicz, Leticia; Sehn, Georgia Ane Raquel; Cavalheiro, Darlene (Revista Principia, 2025)
The pseudofruit of Hovenia dulcis is recognized as a source of bioactive compounds; however, like most fruits, it is highly susceptible to deterioration. Encapsulation techniques are used to protect and stabilize compounds while also minimizing changes in the properties of the supplemented product. This study analyzed freeze-dried pulp of H. dulcis pseudofruit (HD) and pseudofruit pulp microencapsulated by freeze-drying using whey protein concentrate and gum arabic as coating materials (En-HD). The samples (HD and En-HD) were characterized for their physicochemical properties, total phenolic compounds (TPC), antioxidant activity (ABTS and DPPH), α-amylase inhibition, particle size distribution, and scanning electron microscopy. Microencapsulation retained 95.8% of TPC after 75 days of storage at –80 ºC. En-HD showed higher antioxidant activity by the ABTS assay and greater inhibition of the α-amylase enzyme, demonstrating the protective effect of microencapsulation. This technique, with further testing, particularly in vivo, could be promising for managing blood sugar levels. En-HD exhibited a smaller particle size and 76% greater solubility than HD, likely due to the coating materials used in the microencapsulation process and the freeze-drying of the encapsulated sample made with previously freeze-dried HD. En-HD shows potential as a functional additive for use in food industry.